11(-3x+2)-2(1-5x)=-7x-6x

Simple and best practice solution for 11(-3x+2)-2(1-5x)=-7x-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(-3x+2)-2(1-5x)=-7x-6x equation:


Simplifying
11(-3x + 2) + -2(1 + -5x) = -7x + -6x

Reorder the terms:
11(2 + -3x) + -2(1 + -5x) = -7x + -6x
(2 * 11 + -3x * 11) + -2(1 + -5x) = -7x + -6x
(22 + -33x) + -2(1 + -5x) = -7x + -6x
22 + -33x + (1 * -2 + -5x * -2) = -7x + -6x
22 + -33x + (-2 + 10x) = -7x + -6x

Reorder the terms:
22 + -2 + -33x + 10x = -7x + -6x

Combine like terms: 22 + -2 = 20
20 + -33x + 10x = -7x + -6x

Combine like terms: -33x + 10x = -23x
20 + -23x = -7x + -6x

Combine like terms: -7x + -6x = -13x
20 + -23x = -13x

Solving
20 + -23x = -13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '13x' to each side of the equation.
20 + -23x + 13x = -13x + 13x

Combine like terms: -23x + 13x = -10x
20 + -10x = -13x + 13x

Combine like terms: -13x + 13x = 0
20 + -10x = 0

Add '-20' to each side of the equation.
20 + -20 + -10x = 0 + -20

Combine like terms: 20 + -20 = 0
0 + -10x = 0 + -20
-10x = 0 + -20

Combine like terms: 0 + -20 = -20
-10x = -20

Divide each side by '-10'.
x = 2

Simplifying
x = 2

See similar equations:

| 9(4-2n)-3=4-6(3n-5) | | 3ln(x+2)-5ln(5x)=x | | .6x+5=3 | | -5r-5(5+5r)=-5(2+7r) | | -4.0x+2.7-16x=-4.6x+2.7 | | 2x-160250-160250=320420-160250 | | x^2y-X^2+4y-9=0 | | 8+(-8)=-8-8 | | 17x-4y=29 | | -5(-3.25)=4m+8 | | (2t-5)(6t+1)=(4t-3)(3t+6) | | 2c+3=3-4 | | 4(6.25)+3k=34.60 | | 2x-23+2x-17=8 | | Z^2-(i+1)*z+i=0 | | 5x*9-7=3 | | 12-5(3(-1)+2)=17 | | 9(2n)-3=4-6(3n-5) | | 3x^2-36x-27=0 | | 4m+4+7m=13+8m | | 11(-3x-2)-2(1-5x)=-7x-6x | | 5345+n=288195 | | m+3(4)=7 | | F(-3)=2x+4 | | .66m+2=1m-3 | | 53435+n=2888195 | | 4x-2(x-4)=-7+5x-6 | | 47.39=9g+3.92 | | 6+-4+2(6)=14 | | 2(4-8)=16 | | 39+7a=-6(-6a+8) | | 3-2m+3=1-2m+6 |

Equations solver categories